Marine CO2 Patterns in the Northern Salish Sea - Evans, Wiley; Pocock, Katie; Hare, Alex; Weekes, Carrie; Hales, Burke; Jackson, Jennifer; Gurney-Smith, Helen; Mathis, Jeremy T.; Alin, Simone R.; Feely, Richard A. (Frontiers in Marine Science, 2019)
Marine carbon dioxide (CO2) system data has been collected from December 2014 to June 2018 in the northern Salish Sea (NSS; British Columbia, Canada) and consisted of continuous measurements at two sites as well as spatially- and seasonally-distributed discrete seawater samples. The array of CO2 observing activities included high-resolution CO2 partial pressure (pCO2) and pHT (total scale) measurements made at the Hakai Institute’s Quadra Island Field Station (QIFS) and from an Environment Canada weather buoy, respectively, as well as discrete seawater measurements of pCO2 and total dissolved inorganic carbon (TCO2) obtained during a number of field campaigns. A relationship between NSS alkalinity and salinity was developed with the discrete datasets and used with the continuous measurements to highly resolve the marine CO2 system. Collectively, these datasets provided insights into the seasonality in this historically under-sampled region and detail the area’s tendency for aragonite saturation state () to be at non-corrosive levels (i.e. > 1) only in the upper water column during spring and summer months. This depth zone and time period of reprieve can be periodically interrupted by strong northwesterly winds that drive short-lived (~1 week) episodes of high-pCO2, low-pH, and low- conditions throughout the region. Interannual variability in summertime conditions was evident and linked to reduced northwesterly winds and increased stratification. Anthropogenic CO2 in NSS surface water was estimated using data from 2017 combined with the global atmospheric CO2 forcing for the period 1765 to 2100, and projected a mean value of 49 ± 5 µmol kg-1 for 2018. The estimated trend in anthropogenic CO2 was further used to assess the evolution of and pHT levels in NSS surface water, and revealed that wintertime corrosive conditions were likely absent pre-1900. The percent of the year spent above = 1 has dropped from ~98% in 1900 to ~60% by 2018. Over the coming decades, winter pHT and spring and summer are projected to decline to conditions below identified biological thresholds for select vulnerable species.